Cos(x) = cosh(x)?

  1. 1. The problem statement, all variables and given/known data



    2. Relevant equations
    from the identities found on the internet:

    [tex]cos(x)=\frac{(e^{ix}+e^{-ix})}{2}[/tex]

    and

    [tex]cosh(x)=\frac{(e^{x}+e^{-x})}{2}[/tex]



    3. The attempt at a solution

    Assuming for the definition of cosh(x), if we take x as being equal to (ix), then surely this shows that cosh(x)=cos(x)? Can someone explain why this is wrong please? because i can't see it
     
  2. jcsd
  3. Dick

    Dick 25,821
    Science Advisor
    Homework Helper

    It shows cosh(ix)=cos(x), not cosh(x)=cos(x). There's nothing wrong with that.
     
Know someone interested in this topic? Share a link to this question via email, Google+, Twitter, or Facebook

Have something to add?